Perceptions of the United States and the Americans. The collage approach - Hottolal, Petri (Finisterra, 2012)
National and regional stereotypes are difficult to study in a practicalmanner. The Collage method, an experimental method for descriptive research materialanalysis, was designed to that end. It was first tested in a seven-nation survey of college anduniversity students, on the sociotype of the United States and its typical inhabitants. Amongthe samples the one collected in Spain (Pais Vasco) was more critical and sometimes morerealistic in its perceptions than the rest. The criticism focused on the US way of life andespecially on the nation’s role in world politics. The positive aspects of the love-hate relationshipwith the USA were mostly projected on the typically American female, whereasthe male represented the majority of negative connotations. For the students, the typicalUSA was located on the West Coast, in California. The perceptions were clearly influencedby US media entertainment, in addition to more factual news media information